Peningkatan Kapasitas Masyarakat dalam Produksi Hair Oil dan Hand Gel Alami Berbasis Sereh dan Lidah Buaya pada Masyarakat Mitra Gerakan Ekonomi Kaum Ibu (GEMI) Yogyakarta: Enhancing Community Capacity in the Production of Lemongrass and Aloe Vera-Based Natural Hair Oil and Hand Gel for the Gerakan Ekonomi Kaum Ibu (GEMI) Partner Community in Yogyakarta - Tunjung, Woro Anindito Sri; Pamungkas , Kholish Naufal; Kurniawati, Elisabeth; Prihatini, Lusiyana; Nuha, Zahra Karimah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The utilization of local plants as natural ingredients for personal care products has significant potential to enhance community economic value. However, the use of plants such as lemongrass (Cymbopogon citratus) and aloe vera (Aloe vera) among communities is generally limited to basic household purposes, resulting in underutilized economic potential. This community engagement program aimed to improve the knowledge and skills of members of the Gerakan Ekonomi Kaum Ibu (GEMI) group in processing natural materials into personal care products, specifically hair oil and hand gel. The program applied the Asset Based Community Development (ABCD) approach through several stages, including planning, socialization, practical training, evaluation, and the preparation of simple guidelines to support program sustainability. The training method involved demonstrations and hands-on practice using locally available materials. Program evaluation was conducted using pre-test and post-test instruments to measure participants’ knowledge improvement. The results showed a significant increase in participants’ average scores by 21.82%, from 47.27% in the pre-test to 69.09% in the post-test. These findings indicate that the training effectively enhanced community understanding of natural ingredients for personal care products. The resulting products use easily accessible materials, involve simple production processes, and have potential for development as home-based economic activities.